The Humanistic Tradition, Book 5: Medieval Europe And The World Beyond - K Fiero Gloria (Mc Graw Hill, 2005)
"The Humanistic Tradition is quite simply the finest book of its type. Fiero manages to integrate the political, cultural, and social history of the world into one coherent and fascinating whole. It is a masterpiece of scholarship . . . balanced, interesting, easy to read, and consummately beautiful. Our professors praise its accuracy and scope and our students unanimously say it is their favorite textbook." — Sonia Sorrell, Pepperdine University